2010
DOI: 10.1016/j.jaci.2010.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Pest and allergen exposure and abatement in inner-city asthma: A Work Group Report of the American Academy of Allergy, Asthma & Immunology Indoor Allergy/Air Pollution Committee

Abstract: Our work group report details the importance of pest allergen exposure in inner-city asthma. We will focus specifically on mouse and cockroach exposure. We will discuss how exposure to these pests is common in the inner city and what conditions exist in urban areas that might lead to increased exposure. We will discuss how exposure is associated with allergen sensitization and asthma morbidity. Finally, we will discuss different methods of intervention and the effectiveness of these tactics.© 2010 American Aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 74 publications
4
51
0
Order By: Relevance
“…[2][3][4][5] Previous work has highlighted a similarly high prevalence of AR in the urban pediatric population, with underserved children at higher risk for undiagnosed AR 27 and up to two thirds of these children reportedly receiving inadequate or no treatment for AR. 28 Mouse and cockroach allergens have been previously reported to be the two most abundant aeroallergens in many urban communities 15 and our results here, identifying mouse sensitivity by serology as the dominant association with active rhinitis is also consistent with previous work reporting the dominance of mouse over cockroach allergy in asthma outcomes in a similar cohort of urban children. 17 The association between rhinitis and serologic mouse sensitivity was driven largely by children who were positive for mouse sensitivity by both serology and SPT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[2][3][4][5] Previous work has highlighted a similarly high prevalence of AR in the urban pediatric population, with underserved children at higher risk for undiagnosed AR 27 and up to two thirds of these children reportedly receiving inadequate or no treatment for AR. 28 Mouse and cockroach allergens have been previously reported to be the two most abundant aeroallergens in many urban communities 15 and our results here, identifying mouse sensitivity by serology as the dominant association with active rhinitis is also consistent with previous work reporting the dominance of mouse over cockroach allergy in asthma outcomes in a similar cohort of urban children. 17 The association between rhinitis and serologic mouse sensitivity was driven largely by children who were positive for mouse sensitivity by both serology and SPT.…”
Section: Discussionsupporting
confidence: 92%
“…Greater insight into the poorly understood prevalence and triggers of rhinitis in this population could provide an important opportunity to target rhinitis as an approach to improve asthma control. Previous studies showed that allergies to mouse and cockroach, two of the most common indoor allergens, 15 are associated with worse asthma outcomes and are most likely major contributors to asthma morbidity in the urban pediatric population. 16,17 No study has assessed the relationship that sensitization to mouse and cockroach has with rhinitis in urban children with poorly controlled asthma.…”
Section: Introductionmentioning
confidence: 99%
“…43 Exposures to residential allergens also have been associated with living in urban environments of which the majority of this population is comprised of lower income minorities. 44 Our study found that the proportion of Non-Hispanic black and Puerto Rican children with asthma that reported receiving rental assistance was over seven times that of Non-Hispanic white children. The inclusion of direct environmental measures could have been used to better describe differences in prevalence and morbidity among racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 50%
“…Another hypothesis would be that the pattern of environmental exposure to cockroach allergens leading to sensitization may be distinct. In our region, the style of housing is peculiar to warmer climates, with homes and schools being ventilated by keeping windows open; these conditions may not be as conducive to a heavy and sustained cockroach infestation as those observed in US inner-city apartments [2,42]. Consistent with this, levels of cockroach allergens Bla g 1 and Bla g 2 in the homes of asthmatic patients in our area were at least 10-fold lower than those previously reported in the homes of inner-city asthmatic patients in the USA [43].…”
Section: Discussionmentioning
confidence: 99%